Folk classification of the crabs and swimming crabs (Crustacea - Brachyura) of the Mamanguape river estuary, Northeastern - Brazil - da S Q Bezerra Dandara; Nascimento Douglas M; da S Mourão José; Rocha Pollyana D; Ferreira Emmanoela N (BMC, 2009)
Abstract Background Folk taxonomy is a sub-area of ethnobiology that study the way of how traditional communities classify, identify and name their natural resources. The work present was undertaken in two traditional communities (Barra de Mamanguape and Tramataia). The objective of this study was investigate the ethnobiological classification of the local crabs and swimming crabs used by the crustaceous gatherers of the Mamanguape River Estuary (MRE), Paraíba State, Brazil. Methods The methodology used here involved a combination of qualitative methods (open interviews, semi-structured interviews, direct observations, guided tours, surveys, and interviews in synchronic and diachronic situations that crossed-checked and repeated identifications) and quantitative methods (Venn diagram). A total of 32 men and women were interviewed in the two communities. Specimens of the local crustaceans were collected and identified by the harvesters themselves, subsequently fixed in formalin, conserved in 70% ethyl alcohol, identified using appropriate specialized literature, and then deposited in the laboratory of the Zoology Department of the University State of Paraiba. Results The crustaceous gatherers we studied were observed to group crustaceans according to their similarities and differences, producing a hierarchical classification system containing four levels of decreasing taxonomic order: unique beginner, life-form, generic, and specific. A sequential and/or semantic system classification system that is used to classify the ontogeny of the female swimming crab was also identified. Of the nine folk generics identified, 44.5% were monotypic. 55.5% were polytypic and were subdivided into 15 folk specifics. An identification key was elaborated with the data obtained about the folk polytypics generics. Conclusion The detailed knowledge concerning the crabs and swimming crabs revealed by the MRE crustaceous gatherers demonstrates that these people detain a vast knowledge concerning these marine resources. This local knowledge provides a rich but little-known source of information that will aid future ecological and/or zoological studies in the region that will be indispensable for producing management plans to help guarantee the sustainability of these local natural resources.